AL-NUSHUUSH AL-DINIYYAH WA TARJAMATUHA - Mustofa, Bisri (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
Al-Nushuush Al-Diniyyah or divine texts are not the same as other texts. In translating the texts, it does not only need linguistics such as nahwu (sintax), sharaf (morphology) or mufradatÂ  (semantic). Nor the methods usually used in other text. Al-Quran and Al-Hadits have different and special characteristics so that in translating it, a translator have to own interdisciplinary knowledge and master the appropriate translating technique. This is because translating the divine texts (Al-Quran and Al-Hadits) also interpret it so that the most important method in translating the divine texts is Thariqah al-Tarjamah al-Tafsiriyah (Interpreting Method), not literal translation.